2014
DOI: 10.1002/jee.20046
|View full text |Cite
|
Sign up to set email alerts
|

Research‐Informed Policy Change: A Retrospective on Engineering Admissions

Abstract: Background Few studies have investigated how engineering education admission policies contribute to the underrepresentation of specific groups. Transforming these policies may significantly affect who becomes an engineer. This article reports the outcome of using research results to inform change in admission policy at a Midwestern public university.Purpose There were three research questions: Is there statistically significant evidence of admission decision gender bias for engineering applicants? Do affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…They reconfigured the promotion and tenure system to ensure tenure‐track faculty members were conducting research on teaching and learning and supported these changes through a new Office of Faculty Development (Brown & Kurzweil, ). The College of Engineering at Purdue University demonstrated institutional bias in their admission policy with respect to populations underrepresented in engineering—for example, using minimum standardized math test scores—used results of a study to systemically change admissions policy, and showed substantial increases in the percentage of women who matriculated in engineering (Holloway, Reed, Imbrie, & Reid, ). University of Central Florida, a 4‐year institution serving a 33.5% Black or Latinx student population, invested heavily in pairing faculty members with an instructional designer to rebuild their courses in online or blended formats.…”
Section: Interventions That Support Latino Transfer Student Successmentioning
confidence: 99%
“…They reconfigured the promotion and tenure system to ensure tenure‐track faculty members were conducting research on teaching and learning and supported these changes through a new Office of Faculty Development (Brown & Kurzweil, ). The College of Engineering at Purdue University demonstrated institutional bias in their admission policy with respect to populations underrepresented in engineering—for example, using minimum standardized math test scores—used results of a study to systemically change admissions policy, and showed substantial increases in the percentage of women who matriculated in engineering (Holloway, Reed, Imbrie, & Reid, ). University of Central Florida, a 4‐year institution serving a 33.5% Black or Latinx student population, invested heavily in pairing faculty members with an instructional designer to rebuild their courses in online or blended formats.…”
Section: Interventions That Support Latino Transfer Student Successmentioning
confidence: 99%
“…By contrast, few studies have examined the barriers presented by programmatic policies and structures. The study by Holloway, Reed, Imbrie, and Reid () demonstrated how an admissions policy effectively reduced the enrollment of women who could have succeeded in an undergraduate engineering program. Changing this policy removed the obstacle and significantly increased the numbers of women.…”
Section: Changes In the Editorial Boardmentioning
confidence: 99%
“…Two notable observations are made regarding these entering cohorts. First, institutional disparities between application gains and admission gains raised questions about equity in the admissions process, and the admission policies were shown to be in favor of men 13 . As a result, new institutional admissions criteria were implemented in Fall of 2011.…”
Section: Entering Cohortsmentioning
confidence: 99%